2005
DOI: 10.1177/019027250506800303
|View full text |Cite
|
Sign up to set email alerts
|

Mattering and Suicide Ideation: Establishing and Elaborating a Relationship

Abstract: Mattering is the belief that one makes a difference in the lives of others. We explore the effect of mattering on adolescent suicide ideation. The data source is the 2000 Youth At Risk Survey, composed of interviews with 2,004 youths, age 11-18 and screening interviews with their parents. Our analysis reveals that those who matter more are significantly less likely to consider suicide. In addition, we elaborate the relationship between mattering and suicide ideation by postulating a series of intervening varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
74
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(78 citation statements)
references
References 27 publications
(30 reference statements)
3
74
0
Order By: Relevance
“…Previous studies have pointed to that recognizing the suicidal patient—in terms of ‘you exist, you are not alone and your experiences are acknowledged’—is essential (Cutcliffe et al, 2006; Talseth et al, 1999). Such care may increase the person’s belief that he/she matters to others in the world, which has been associated with increased self-esteem and decreased suicide ideation (Elliott, Colangelo, & Gelles, 2005). Our findings add to this literature by indicating that in order to provide good treatment and care and to make the patient feel valuable, it is important that the mental health workers employ their personal qualities as empathic fellow human beings and provide the patients with a sense of companionship.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have pointed to that recognizing the suicidal patient—in terms of ‘you exist, you are not alone and your experiences are acknowledged’—is essential (Cutcliffe et al, 2006; Talseth et al, 1999). Such care may increase the person’s belief that he/she matters to others in the world, which has been associated with increased self-esteem and decreased suicide ideation (Elliott, Colangelo, & Gelles, 2005). Our findings add to this literature by indicating that in order to provide good treatment and care and to make the patient feel valuable, it is important that the mental health workers employ their personal qualities as empathic fellow human beings and provide the patients with a sense of companionship.…”
Section: Discussionmentioning
confidence: 99%
“…Schlossberg and colleagues noted that to the degree that people perceive they do not matter, they will feel marginalized or disconnected. Moreover, this sense of insignificance may lead to existential meaninglessness and social isolation for some people and individuals may question their very existence and engage in self-destructive behavior (Elliott, Colangelo, & Gelles, 2005;Marshall, 2001;Schlossberg, 1989). In contrast, those who perceive a sense of social purpose and meaning for their life are more likely to feel significant to key people in their lives (Marshall, 2001), including to individuals in a college setting (Elliott et al, 2005;France, 2011;Schlossberg, 1989;Schlossberg et al, 1989;Tovar, Simon, & Lee, 2009).…”
Section: Definition Of Matteringmentioning
confidence: 99%
“…Mattering has also been described as being part of the self-concept and that it exercises an influence on our psychological well-being (Dixon-Rayle, 2006;Dixon-Rayle & Chung, 2007;Dixon-Rayle & Myers, 2004;Dixon & Kurpius, 2008;Elliott, 2009;Elliott et al, 2005;Elliott, Kao, & Grant, 2004;Josselson, 1998;Rosenberg, 1985;Rosenberg & McCullough, 1981), especially during the period of adolescence, young adulthood, and senescence. As will be noted below, a low self-concept and a low sense of interpersonal and societal mattering has been associated with depressive symptoms, anxiety, low self-esteem, suicide ideation, and generalized psychological distress.…”
Section: Mattering and The Self-conceptmentioning
confidence: 99%
See 1 more Smart Citation
“…Psychologists have suggested that the desire to be valued and needed by others (i.e., the pursuit of social worth) is a basic human motivation (McAdams & de St. Aubin, 1992;Ryan & Deci, 2000). Experiencing social worth makes individuals feel that their actions matter in the life of other people (Elliott, Colangelo, & Gelles, 2005;Rosenberg & McCullough, 1981), which heightens their sense of belongingness (Baumeister & Leary, 1995;Keyes, 1998). In the work context, scholars have proposed that employees interpret interpersonal cues from others as affirming or disaffirming of who they are as a person, which leads to one's sense of confirmed worth as a human being (Wrzsniewski, Dutton, & Debebe, 2003).…”
Section: Relational Self-affirmation and Feelings Of Social Worthmentioning
confidence: 99%